The Application of the Healthy Feet Application for Educational Media for the Elderly Those Experiencing Foot Problem: Healthy Feet - Iis Noventi; Siti Maimunah; Shobihatus Syifak; Siti Nur Hasina; Rahmadaniar Aditya (Community Development Journal, 2023)
One of the changes in physical condition due to aging is in the musculoskeletal system, namely joint disorders, which is a frequently encountered disease that is closely related to the aging process. Joint pain is a common disease in the elderly population. This is because, apart from age, joint pain occurs because many elderly people cannot control their lifestyle. There are many actions to deal with pain complaints in the elderly, but both the elderly and their families forget to remember what they were taught when they were there Hospital or Posyandu. Efforts to ensure comfort, reduce complaints and improve the quality of life for elderly people with leg pain must create methods to make it easier to remember what has been taught. The aim of this service is to provide an alternative treatment for elderly people with leg complaints by creating an application as a reminder of the actions to overcome what has been taught previously. The subjects of this service are 30 elderly people who experience foot complaints. This activity is carried out by teaching how to operate an application via Android which contains a menu on how to screen foot health based on complaints, then the elderly can find out the score whether their feet are healthy or have neuropathy and a menu on how to deal with them. problems based on the score results. Assistance for elderly people who experience foot complaints for a period of 1 month (June – July 2023) by implementing the Healthy Feet Application as an educational medium for elderly people who experience foot problems. From this activity, a comparison of the level of knowledge about foot health was obtained before the educational method with the Healthy Feet application was provided and after the education was given, there was a significant increase in knowledge about foot health with a value of p = 0.000 < 0.05. Applying the Healthy Feet application to determine the condition of foot health and efforts to deal with complaints can increase knowledge and self-awareness of foot health